Compañeros and Protagonismo: The Ethics of Anti‐Neoliberal Activism and the Frente de Pueblos en Defensa de la Tierra (FPDT) of Atenco, Mexico. - Stone, Livia K. (Journal of Latin American & Caribbean Anthropology, 2019)
Networks of anti‐neoliberal social movements in Mexico internally police what they refer to as protagonismo (activities benefitting the individual), and attempt to cultivate ethical activist practices surrounding selflessness and collectivity. This article examines the fraught meanings of protagonismo and ethical activist practice in the particular history and experiences of the Frente de Pueblos en Defensa de la Tierra (FPDT) from San Salvador Atenco. The article presents brief histories of the FPDT and the set of activist virtues I refer to as compañerismo. These histories come together in the context of state violence and co‐optation in which activists deploy ideas of protagonismo and compañerismo as pragmatic organizational and safety strategies as well as ethical regimes. I argue that through their emphasis on collectivity, contemporary ideas of compañerismo in the FPDT pose challenges to liberal democratic political processes as well as neoliberal conceptions of citizenship.[Indigenous people, Mexico, politics, social anthropology, social movements]